Tahap keberkesanan dan kepuasan pengurusan penyenggaraan fasiliti Jalan Persekutuan di Jabatan Kerja Raya Malaysia - Yahaya, Rusmizi (2010)
This study aimed to evaluate the effectiveness and satisfaction of the federal road maintenance management facilities in the PWD, especially in Kedah Darul Aman. The effectiveness and statisfaction of the federal road maintenance management facilities in the PWD is very important because the inconvenience of road users will have direct impact on government delivery system and national development. The first objective of this study was to determine the effectiveness and statisfaction of the federal road maintenance management is currently maintained by the concessionaire and the government appointed and a second objective is to identify proposals for improvements that can be taken by the PWD in particular, the Government generally on the performance of work Federal Roads maintenance more effective. From the literature review, the authors have identified some of the parameters and the main elements for measuring the effectiveness of the management of the maintenance of essential elements such as policy and structural maintenance, approach, method of maintenance, scheduling and execution of work, information management and CMMS, maintenance contract management, parts management, human resource management, financial aspects, and continuous improvement. The data collection was made through the study interviews and questionnaires. Through a random sampling method, data taken from various divisions / district in Kedah State PWD. The data are descriptive and inferential statistical techniques such as Summarize Frequencies, Cross Tabulation and Pearson Correlation. All results of this study was obtained through the output of the computer software; SPSS and Microsoft Excel 2007. Findings indicate that aspects of compliance with major elements of facilities management for the federal road maintenance in the PWD is only effective on normal levels and have enhanced its effectiveness.